The effect of New Zealand Superannuation eligibility age on the labour force participation of older people - Roger Hurnard (New Zealand Government, The Treasury, 2005)
New Zealand experienced a sharp rise in labour force participation rates among older people over the period 1991/2001. This stands in contrast to the experience of most other OECD countries where such participation rates have been in steady decline. The predominant reason for this turnaround was that the age of eligibility for New Zealand Superannuation, the universal public pension, was raised from 60 to 65 over a nine-year period. Combining an earlier reduction in eligibility age with this later policy reversal, this paper estimates the effect of public pension eligibility on the labour force participation of different age groups. The paper discusses why particular features of New Zealand?s pension system mean that the strength and rapidity of the response to a rise in eligibility age might not be repeatable in other settings.
Keywords: I38; J26; 330; public pensions; labour force participation; retirement; New Zealand